Dimensions of Students' Mathamatical Creative Thinking Ability in the PostCovid-19 Pandemic - Khuzaini, Nanang; Ili, La; Sahidin, Latief; Rumasoreng, Muhammad Irfan (FKIP Universitas Lampung, 2022)
Mathematical Creative Thinking Ability is a means of finding solutions and solving problems universally. This study aims to analyze students' mathematical creative thinking skills after the covid-19 pandemic. The research subjects were 100 SMA/MA students in DIY. The research method used is descriptive quantitative assisted by the LISREL program. The analytical tool used is structural equation modeling to analyze the dimensions of mathematical creative thinking which consists of four indicators, namely flexible, fluent, elaborative, and evaluative thinking. The results showed that the students' mathematical creative thinking ability was at a moderate level above 80% with a loading factor value greater than 0.3 and a t-value above 1.96. Of the four dimensions, the indicator of elaborative thinking ability is the most dominant in contributing to and influencing the sub-indicator, namely developing students' ideas. Keywords: mathematical creative thinking, structural equation modelling, Covid-19 pandemic DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1328-1336